(untitled) (Research, Society and Development, 2021)
Introduction: Myiasis is a pathological condition characterized by the infestation of dipterous larvae in living tissues or necrotic cavities these larvae develop as parasites being fed by the host’s tissues. This condition can be classified as primary, which consists of the development of larvae from living tissue (biophage), or secondary, which is characterized by its development from dead tissue (necrophages). Objective: To report a case of submandibular myiasis in the right region, treated with ivermectin after surgical therapy. Case report: A 46-year-old male patient attended the State General Hospital complaining of a lesion in the submandibular region. Clinical and imaging examination confirmed the diagnosis of myiasis. Afterwards, the patient was taken to the operating room, where the mechanical removal of the larvae was performed, followed by disinfection of the lesion and medication prescription. The lesion responded well to treatment with ivermectin 150 μg/kg, administered orally, in a single dose. Conclusion: Thus, it was observed that the removal of all larvae associated with antibiotic therapy is a good treatment for patients with myiasis in the oral and maxillofacial region.